The Dark Side of Tourism's Implications on the 2016 Italian Earthquake: Results From a Structural Equation Modeling Study - Kulaga, B.; Cinti, A.; Mazzocchini, F.J. (Journal of Strategic Innovation and Sustainability, 2020)
Even though growing academic attention on dark tourism is a fairly recent phenomenon, among the various reasons for travelling, death-related ones are very ancient; the darker side of human nature has always been fascinated and curious about death. This study proposes to describe the phenomenon of dark tourism related to the 2016 earthquake in Central Italy. The primary objective is to examine the motivation-experience relationship in a dark tourism site, using the structural equation model, applied for the first time to a dark tourism research in 2016, in a study carried out after the Beichuan earthquake (BER). The findings are derived from primary data compiled from 361 tourists by conducting a Likert scale survey. It was used the structural equation model to examine the motivation behind dark travel and how this experience can influence the motivation and emotional reaction of tourists. Findings are partially in line with the previous study mentioned above, indicating that differences in the socio-cultural context play a role.